STREAMING SELVES: VULGAR LANGUAGE, CODE-MIXING, AND HYBRID COMMUNAL IDENTITY OF AN INDONESIAN LIVE-STREAMER - Fariq Shiddiq Tasaufy; Cicilia Deandra Maya Putri; Slamet Setiawan; Ayunita Leliana; Lina Purwaning Hartanti; Imam Hanafi; Noerhayati Ika Putri (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2025)
This paper examines how an Indonesian live-streamer and his audiences create a hybrid communal identity by using vulgar language and code-mixing with reference to the popular YouTube livestream @deandeankt. With the digital medium transforming the world into a global village, the streaming culture in Indonesia provides a distinct perspective into how localized linguistic practices interact with global trends in the internet. The interpretivist-constructivist paradigm applied in the current case study research was aimed at understanding the way language and interaction produced hybrid identities. It gathered linguistic and paralinguistic data of @deadndeakt’s livestream for 90 minutes with netnography and thematic analyses. According to the study, abusive swearing (e.g.,